REPRESENTASI IDEOLOGI MINANGKABAU DALAM FILM SURAU DAN SILEK DITINJAU DARI KAJIAN SEMIOTIKA - Fitri, Dynia (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2018)
This film is based on phenomena that exist in society and are presented in the form of moving images. Surau and Silek movies are one of the fictional films that elevates the local cultural wisdom of the Minangkabau people, West Sumatera. This Movie tells the story of the culture of education in Surau, which is currently rare to find. This research seeks to reveal how a director represents Minangkabau ideology in the Surau and Silek Movies. The type of research used is qualitative by using Roland Barthes's semiotic method which develops two systems, namely signified and signifier and meanings contained and what they wish to convey. In the film Surau and Silek, religious and cultural values reflected in it have the meaning to change the perception of silat in Minang as the formation of the root character of Islam and can revive the surau.